A Formative–Summative Evaluation of Qur’anic Memorization Learning in Primary Education Using Scriven’s Model - Kurnia, Eni; Muhibbin, Ahmad; Sumardi, Sumardi (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study examines the implementation of the Tahfidz Al-Qur’an program as a core curricular component in Islamic elementary schools, focusing on its learning processes and contributions to character and religious education. Using a qualitative descriptive approach, the study seeks to understand how Tahfidz learning is structured, implemented, and experienced within everyday instructional practices at the primary education level. Data were collected through classroom observations, in-depth interviews with Tahfidz teachers and school leaders, and analysis of curriculum documents and learning records. The findings indicate that the Tahfidz program is institutionally embedded within the school curriculum and consistently implemented across grade levels with learning targets adjusted to students’ developmental stages. The learning process is characterized by structured routines, repetitive memorization practices, intensive teacher–student interaction, and the integration of adab and discipline into daily learning activities. In addition to memorization outcomes, the program contributes to the development of positive learning habits, self-discipline, and sustained spiritual engagement among students. However, the evaluation of Tahfidz learning remains largely outcome-oriented, with limited emphasis on systematically documenting learning processes. Overall, the study highlights the Tahfidz Al-Qur’an program as a holistic educational approach that integrates cognitive, affective, and behavioral dimensions of learning from an early age, while emphasizing the importance of strengthening formative and process-oriented evaluation practices to enhance its effectiveness.